Toward solvent screening in the extractive desulfurization using ionic liquids: QSPR modeling and experimental validations. (15th October 2021) - Gorji, Ali Ebrahimpoor; Sobati, Mohammad Amin; Alopaeus, Ville; Uusi-Kyyny, Petri
Graphical abstract: Highlights: QSPR models were developed for prediction of distribution coefficient of thiophene. A large dataset with 84 different ternary system and 763 data points was employed. Cation, anion, and hydrocarbon effect on the thiophene distribution was studied. LLE data for a large number of new ternary systems was predicted using QSPR model. The validity of the QSPR model was confirmed using new measured experimental data. Abstract: In the present study, the effects of different structures of the involved compounds (such as cation, anion, and hydrocarbon) in the ternary systems on the distribution coefficient of the thiophene between ionic liquid and hydrocarbon-rich phases have been studied using Quantitative Structure-Property Relationship (QSPR). By a comprehensive literature survey, the experimental data of the distribution of thiophene for 84 different ternary systems with 763 data points have been collected. The data set includes 14, 10, and 10 different cation, anion, and hydrocarbon structures, respectively. A general QSPR model has been developed to evaluate the simultaneous effect of the hydrocarbon structure, the cation structure, and the anion structure on the thiophene distribution between the hydrocarbon and ionic liquid-rich phases. The selected molecular descriptor in this model was simple descriptor of the number of carbon atom (nC) for the cation structure, the number of nitrogen atom (nN) for the anion structure, and "Pol" for the hydrocarbon structure. The outcome of the internal validation, the external validation, and the statistical evaluation of the final QSPR models (R 2  = 0.91, %AARD = 17.28) confirmed the acceptable prediction capability. The Liquid-Liquid Equilibrium (LLE) data has also been generated using the QSPR approach for a vast number of non-studied ternary systems for the first time. The LLE data of four different ternary systems ([C2 MIM][EtSO4 ] (1) - Thiophene (2) - Cyclohexane, Methyl cyclohexane, n -Nonane, n -Decane (3)) was measured experimentally. The comparison of the measured experimental data and the predicted data using the developed QSPR model confirmed the validity of the QSPR developed model, again.